2019
DOI: 10.3892/ol.2019.10948
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyruvate kinase M2 in anticancer therapeutic treatments (Review)

Abstract: Cancer cells are characterized by a high glycolytic rate, which leads to energy regeneration and anabolic metabolism; a consequence of this is the abnormal expression of pyruvate kinase isoenzyme M2 (PKM2). Multiple studies have demonstrated that the expression levels of PKM2 are upregulated in numerous cancer types. Consequently, the mechanism of action of certain anticancer drugs is to downregulate PKM2 expression, indicating the significance of PKM2 in a chemotherapeutic setting. Furthermore, it has previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 101 publications
0
36
0
1
Order By: Relevance
“…Up-regulation of PKM2 is a hallmark of numerous tumor types, making it a potential therapeutic target [ 87 ]. Targeting PKM2 with some small molecules has been used in the preclinical studies to interfere with tumor growth.…”
Section: Pkm2 As a Therapeutic Targetmentioning
confidence: 99%
“…Up-regulation of PKM2 is a hallmark of numerous tumor types, making it a potential therapeutic target [ 87 ]. Targeting PKM2 with some small molecules has been used in the preclinical studies to interfere with tumor growth.…”
Section: Pkm2 As a Therapeutic Targetmentioning
confidence: 99%
“…Given that PKM2 overexpression is highly associated with advanced ovarian cancers, the development of novel anticancer drugs or therapeutics that can target PKM2 could be an important strategy to improve the survival rate of patients with PKM2-overexpressing ovarian cancer. To date, several PKM2 inhibitors, including shikonin, metformin, vitamin K, and temozolomide, have been identified [10]. Our study focused on the effects of compound 3K, a specific PKM2 inhibitor, in ovarian cancer cells, and we mechanistically demonstrated that the effects of compound 3K were mediated by the targeting of metabolism for therapeutic benefit.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that autophagy is impaired by the activation of the Akt/mTOR pathway in ovarian cancer cells. Therefore, autophagy is heavily regulated by the kinase mTOR [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its toxicity and poor solubility limit its application. 211 Recent studies have found that metformin can also induce tumor cell death and increase sensitivity to chemotherapy drugs by inhibiting PKM2 in osteosarcoma. 212 LDHA is located at the bifurcation point of glycolysis and oxidative phosphorylation.…”
Section: Treatments For Aerobic Glycolysismentioning
confidence: 99%